Effect of Echinochrome A on Submandibular Gland Dysfunction in Ovariectomized Rats - Ji-Min Kim; Sung-Chan Shin; Yong-Il Cheon; Hyung-Sik Kim; Gi-Cheol Park; Hyoung-Kyu Kim; Jin Han; Jung-Eun Seol; Elena A. Vasileva; Natalia P. Mishchenko; Sergey A. Fedoreyev; Valentin A. Stonik; et al. (Marine Drugs, 2022)
Post-menopausal dry mouth or xerostomia is caused by reduced salivary secretion. This study aimed to investigate the efficacy of echinochrome A (Ech A) in alleviating submandibular gland dysfunctions in ovariectomized rats that mimic menopause. Female rats that were eight-weeks-old were randomly divided into SHAM-6, -12; OVX-6, -12; and ECH-6, -12 groups (consisting of 6- and 12-weeks post-sham-operated, ovariectomized, and Ech A-treated ovariectomized rats, respectively). The ECH groups had lower body weight than OVX but similar food intake and estradiol or estrogen receptor β expression. However, the ECH groups had lower mRNA expression of sterol-regulatory element binding protein-1c (Srebp-1c), acetyl-CoA carboxylase (Acc), fatty acid synthase (Fasn), cluster of differentiation 36 (Cd36), and lipid vacuole deposition than OVX mice. Moreover, reactive oxygen species (ROS), malondialdehyde (MDA), and iron accumulation were lower in the ECH than in the OVX groups. Fibrosis markers, transforming growth factor β (Tgf-βI and Tgf-βII mRNA) increased in the OVX than SHAM groups but decreased in the ECH groups. Aquaporin (Aqp-1 and Aqp-5 mRNA) and mucin expressions were downregulated in the OVX groups but improved with Ech A. In addition, Ech A prevented post-menopausal salivary gland dysfunction by inhibiting lipogenesis and ferroptosis. These findings suggest Ech A as an effective remedy for treating menopausal dry mouth.